Математичне моделювання гідрохімічного режиму поверхневих вод річок Верещиця та Коропець (басейн Дністра) - Дудок, І.; Ніколенко, О. (Геологія і геохімія горючих копалин, 2010)
Побудовано імітаційні математичні моделі гідрохімічного режиму Великолюбінського ставка (басейн р. Верещиця) та ставка м. Підгайці (басейн р. Коропець)
для з’ясування можливості їхнього використання в практиці управління якістю водних ресурсів малих річок. Розробку моделей здійснювали шляхом безпосередньої
побудови камерної моделі на основі просторового осереднення процесів і складання
балансових рівнянь. Для оцінки змін гідрохімічного режиму було використано результати визначень концентрацій біогенних речовин та сульфат- і хлорид-іонів. Складено математичні моделі для різних сезонів, які свідчать про те, що у ставках вода
частково очищається від забрудників, чому сприяють процеси, які відбуваються в
них (седиментаційні, процеси сорбції–адсорбції, осадження, розчинення). The simulation mathematical models of hydrochemical regime of the ponds of Velykyi Lubin (the basin of the River Vereshchytsya) and Pidhaitsi (the basin of the River
Koropets) were constructed for identification of opportunities for usage of such models in
the practice of water resources quality management in small rivers.
The expeditionary method was used for the study of the ecological state of the basins
of the rivers Vereshchytsya and Koropets. All information considering the natural conditions, the contents of nitrogen compounds in water (which were estimated on-site) was
gathered during the visits to the research facilities. Analyses of macro- and mesocomponent composition of the natural water basins were accomplished. The processing of infor
mation was executed using the mathematical modelling of the hydrochemical regime of
89
the surface water. The computational models for studying changes in the concentration of
nutrients, chloride and sulphate ions in the examined objects and forecasting of their ecological condition were created. Development of mathematical simulation models of the
hydrochemical regime of the pounds of Velykyi Lubin and Pidhaitsi was carried out
through direct construction of a chamber model based on the spatial averaging of processes and composed of balance equations. The results of estimation of sulphate and chloride-ions concentrations were used for the evaluation of hydrochemical regime alterations.
As a result, the mathematical models for different seasons were formed.